The biological effects of different LED wavelengths in the health field. A review - Carmello, Juliana Cabrini [UNESP]; Barbugli, Paula Aboud [UNESP]; Jordão, Cláudia Carolina [UNESP]; Oliveira, Rui; Pavarina, Ana Claudia [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: the use of light emitting diodes (LED) in domestic and public vias have increased in the last 20 years. In addition, the LED light has been used as a light source for medical applications. Objective: since humans are increasingly exposed to LEDs, there is an urgency to investigate the possible biological effects on tissues caused by this exposure. So, researchers have been focused their investigations in the application of this light in the health field. Material and method: in this review, a search in important databases was performed on the biological effects caused after application of different LED light protocols in in vitro and in vivo studies. Result: although most published papers have shown positive results, some of them reported negative biological effects of light LEDs technology on humans’ cells/tissues. Conclusion: therefore, the comprehension of the biological effects caused by light LEDs will provide a better assessment of the risks involved using this technology.
Os efeitos biológicos de diferentes comprimentos de onda de LED na área da saúde. Uma revisão
Keywords: LED; LED biological effects; light emitting diode; light sources; Phototherapy